Evaluation of the thermal damages in inlet engine valves varying the grinding wheels and the cutting fluids - Bianchi, Eduardo Carlos [UNESP]; Silva, Eraldo Janonne da; Aguiar, Paulo Roberto de [UNESP]; Catai, Rodrigo Eduardo [UNESP] (Escola de Minas, 2003)
Nesse artigo é apresentada uma pesquisa experimental sobre os danos térmicos que aparecem nas válvulas de admissão dos motores após passarem pelo processo de retificação. Foram utilizados, nessa experimentação, quatro tipos de fluidos de corte e dois rebolos (CBN e Al2O3), sendo analisadas a tensão residual, a microdureza e a microestrutrura das peças fabricadas com esses materiais. Esses fluidos e rebolos resultaram em diferentes tipos de tensões residuais. O óleo de corte, por exemplo, induziu nas peças tensões residuais de compressão. em relação ao rebolo de CBN, devido às melhores propriedades de seus grãos abrasivos, estes proporcionaram tensões de compressão para todos os fluidos testados. em relação às alterações microestruturais, notou-se que nenhuma alteração térmica foi detectada nas peças, embora a inexistência de alterações microestruturais nem sempre sugerem que tensões residuais favoráveis foram obtidas.

This paper presents an experimental research in which the thermal damage in inlet engine valves grinding was evaluated. Four different cutting fluids and two grinding wheel were tested and were analyzed the workpiece residual stress, the micro hardness and the optical observation of the workpiece microstructure. The cutting fluid and the grinding wheel types adopted resulted in different types of residual stress. The cutting oil resulted in compressive residual stresses, even using the conventional wheel. The CBN wheel, due to the best proprieties of its grains resulted in compressive residual stresses for all fluids tested by the reducing of the grinding energy and its easier dissipation from the grinding zone. The microstructure investigations showed that the source of the tensile residual stresses observed was the thermal cycles imposed. No microstructure alterations were detected. Although, the absence of microstructure alterations not always suggests that favorable residual stresses can be obtained.
Keywords: Retificação; fluidos de corte; rebolos; tensões residuais; danos térmicos; válvulas; Grinding; cutting fluids; grinding wheel; residual stresses; thermal damage; valves